Factors contributing to burnout among healthcare workers during covid-19 in Sabah (East Malaysia) - Nicholas Tze Ping Pang; Noor Melissa Nor Hadi; Mohd Iqbal Mohaini; Assis Kamu; Chong Mun Ho; Eugene Boon Yau Koh; Jiann Lin Loo; Debbie Quah Lye Theng; Walton Wider (Multidisciplinary Digital Publishing Institute, 2022)
The third wave of COVID-19 in Malaysia has significantly strained the healthcare system of the country and increased the level of burnout among the healthcare workers (HCWs) in the country. Therefore, this study aimed to identify the various factors associated with burnout among HCWs. A cross-sectional study was conducted among 150 HWCs in Kota Kinabalu, Sabah, Malaysia. An online survey was administered using the Copenhagen Burnout Inventory, Multidimensional Scale of Perceived Social Support, Brief COPE, and Fear of COVID-19 scales. Pearson correlations were assessed amongst all variables. Subsequently, a multiple linear regression analysis was performed using burnout dimensions as dependent variables. Multiple linear regression results showed: (a) lower work-related burnout (β = −0.217, p < 0.01) among married HCWs; (b) higher personal-related burnout (β = 0.228, p < 0.01), work-related burnout (β = 0.425, p < 0.01), and client-related burnout (β = 0.359, p < 0.01) among doctors; (c) fear towards COVID-19 was significantly associated with client-related burnout (β = 0.243, p < 0.01); (d) an avoidant coping strategy was significantly associated with personal-related burnout (β = 0.322, p < 0.01); (e) social support from family was significantly associated with personal-related burnout (β = −0.264, p < 0.01), work-related burnout (β = −0.186, p < 0.05), and client-related burnout (β = −0.326, p < 0.01); (f) and social support from friends was significantly associated with work-related burnout (β = −0.202, p < 0.05). This study demonstrated significant theoretical contributions and clinical implications in the healthcare system in Sabah by addressing the impact of various factors on burnout among HWCs.